2010
DOI: 10.1188/10.onf.e411-e418
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Symptom Severity and Symptom Interference, Education, Age, Marital Status, and Type of Chemotherapy Treatment in Israeli Women With Early-Stage Breast Cancer

Abstract: Evidence-based symptom profiles for different chemotherapy protocols are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
(43 reference statements)
3
19
0
5
Order By: Relevance
“…Multiple studies have documented the wide range of serious physical and psychological symptoms associated with cancer and adverse effects of cytotoxic medications used in chemotherapy regimens (Ryan, 1996;Stanton et al, 2005;Breen et al, 2009;Syvak et al, 2012). Pain, fatigue, lack of appetite, dry mouth, mucositis, dyspnea, constipation, diarrhea, anorexia, insomnia, nausea, vomiting, cognitive difficulties, depression and anxiety are common symptoms experienced by cancer patients who are undergoing chemotherapy (Ryan, 1996;Prigozin et al, 2010). Distress from multiple concurrent symptoms, both physical and psychological, often leads patients to delay seeking treatment or, later in the course of their disease, to terminate treatment early (Syvak et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Multiple studies have documented the wide range of serious physical and psychological symptoms associated with cancer and adverse effects of cytotoxic medications used in chemotherapy regimens (Ryan, 1996;Stanton et al, 2005;Breen et al, 2009;Syvak et al, 2012). Pain, fatigue, lack of appetite, dry mouth, mucositis, dyspnea, constipation, diarrhea, anorexia, insomnia, nausea, vomiting, cognitive difficulties, depression and anxiety are common symptoms experienced by cancer patients who are undergoing chemotherapy (Ryan, 1996;Prigozin et al, 2010). Distress from multiple concurrent symptoms, both physical and psychological, often leads patients to delay seeking treatment or, later in the course of their disease, to terminate treatment early (Syvak et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Such consequences of depression may exacerbate the already stressful process of chemotherapy. Although chemotherapy side effects have been shown to impact daily functioning in women with breast cancer, it is not clear whether an association exists between chemotherapy-related symptom burden and depression [15,16]. Anxiety is often comorbid with depression after a diagnosis of breast cancer and may be heightened during chemotherapy [8,17].…”
Section: Introductionmentioning
confidence: 98%
“…It was composed of four wellbeings of participants (physical, social/family, emotional and functional) included breast cancerspecific subscale. It was rated by 5-point Likert scale not at all (0) to very much (4). All items of the FACT-B were calculated by averaging all items in every subscale and total scores were multiplied.…”
Section: Methodsmentioning
confidence: 99%
“…Thirteen out of 28 symptoms were reported in more than 50% of patients with breast cancer undergoing chemotherapy regimen 3 . The most common symptoms reported were fatigue, sleep disturbance, drowsiness, distress and sadness, hot flashes and sweats, and pain [4][5] . Suwisith and colleagues revealed that the participants stated mild to moderate level of symptom severity 3 .…”
Section: Introductionmentioning
confidence: 99%